Hubungan Iklan "Ingat Pesan Ibu" dengan Penerapan Protokol Kesehatan - Vianqa Azizah; Rini Rinawati (Bandung Conference Series: Communication Management, 2022)
Abstract. In human civilization, communication becomes unimportant. Without communication, everything humans do is hampered without symbols, words, and meanings. One form of written communication that most people often use is advertising. The existence of advertising cannot be separated from verbal and visual elements. Just like public service advertisements “remember the message of mother” which presents attractive visuals and convincing verbal so that the audience who sees the advertisement will be persuaded to carry out health protocols. Advertisements here have a meaning as a reminder for public health, especially student health. Currently the world including our country Indonesia is experiencing a pandemic due to the Covid-19 Virus. This virus is already endemic and is being used as a global health emergency. The purpose of this study was to determine whether or not there is a relationship between the "Remember Mother's Message" advertisement and the application of health protocols to students of the Faculty of Communication Science, Islamic University of Bandung, class 2017. The methodology used in this study is a quantitative method with a correlation approach, while the analysis in this study uses several tests by distributing questionnaires and literature studies. The theory that supports this research is S-O-R. The results of this study, there is a relationship between the "Remember Mother's Message" advertisement and the application of health protocols to students of the Faculty of Communication Sciences, Islamic University of Bandung, class of 2017. Abstrak. Dalam peradaban manusia, komunikasi menjadi unsur penting. Tanpa komunikasi, semua yang dilakukan manusia terasa terhambat tanpa adanya simbol, kata, dan makna. Salah satu wujud komunikasi tulis yang kerap digunakan kebanyakan orang yaitu periklanan. Keberadaan iklan tidak terlepas dari unsur verbal dan visual. Sama halnya seperti iklan layanan masyarakat “ingat pesan ibu” yang menghadirkan visual menarik dan verbal yang persuasive agar khalayak yang melihat iklan tersebut menjadi terpersuasi untuk menjalankan protokol kesehatan. Iklan disini memiliki arti sebagai pengingat untuk kesehatan masyarakat terutama kesehatan Mahasiswa. Saat ini dunia termasuk negara kita Indonesia sedang mengalami pandemi akibat Virus Covid-19. Virus ini sudah mewabah dan menjadikannya sebagai darurat kesehatan global. Tujuan dari penelitian ini adalah untuk mengetahui ada atau tidaknya hubungan antara Iklan “Ingat Pesan Ibu” dengan Penerapan Protokol Kesehatan pada Mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Bandung angkatan 2017. Metodelogi yang digunakan penelitian ini adalah metode kuantitatif dengan pendekatan korelasional sedangkan analisis dalam penelitian ini menggunakan beberapa uji dengan penyebaran angket serta studi kepustakaan. Teori yang mendukung penelitian ini S-O-R. Hasil dari penelitian ini, adanya Hubungan antara Iklan “Ingat Pesan Ibu” dengan Penerapan Protokol Kesehatan pada Mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Bandung angkatan 2017.